A profile of the mortgage crisis in a low-and-moderate-income community - Lynn Fisher; Lauren Lambie-Hanson; Paul S. Willen (Federal Reserve Bank of Boston, 2010)
This paper assesses the impact of the mortgage crisis on Chelsea, Massachusetts, a low-and moderate income community of 35,000 adjacent to Boston. After years of rapid growth, house prices started falling in 2005. According to our repeat-sales indices, by the end of 2009 prices had fallen by as much as 50 percent from their peak. Foreclosures have soared and lenders have repossessed or allowed short sales on more than 330 homes, resulting in a forced exit of at least one in 30 of the town's households. A large fraction of the foreclosed properties were twoor three-family homes, so the number of households affected by the crisis undoubtedly extends beyond the number of foreclosures. But there is some positive news. After a slow start, servicers appear to have become far more efficient at selling foreclosed properties, so the stock of real estate owned properties has been falling since 2008. For the most part, homeowners who bought prior to the peak of the boom have so far avoided selling in the moribund market and thus are poised to gain if and when the market recovers. In addition, the crisis has not prevented homeowners from maintaining and improving their properties: both the number and the dollar value of building permits have held up well even for those homeowners who have bought recently and likely have negative equity in their homes.
Keywords: R1; G01; 330; Finanzmarktkrise; Subprime-Hypothek; Immobilienmarkt; Zwangsvollstreckung; Kommunale Wirtschaftsentwicklung; USA